Meningkatkan Hasil Belajar Dengan Menggunakan Model Pembelajaran Project Based Learning (PjBL) Tema 1 Selamatkan Makhluk Hidup Subtema 2 Hewan Sahabatku Pembelajaran 2 Di Kelas VI-B SD Negeri 104201 Kolam - Rasputri, Indah (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
The problem in this study was the students classical mastery in class VI-B SD Negeri 104201 Kolam who had not achieved 85% classical completeness. This is because the selection of the learning model that the teacher applies is not by the material at Tema 1 Selamatkan Makhluk Hidup Subtema 2 Hewan Sahabatku Pembelajaran 2. In the implementation of integrative thematic learning that the teacher has not maximized the use of TPACK-based technology media, and the implementation of learning methods is still dominated by the lecture method so that it is teacher-centered. This type of research is class action research (Classroom Action Research), with the research subject being Class VI-B Students of SD Negeri 104201 Kolam for the 2022/2023 academic year. A total of 21 students, with details of 9 male students and 12 female students. The object of this research is the learning outcomes of students. This research was carried out in two learning cycles. 4 (are four) stages in each cycle, the cycle are planning, implementation, observation, and reflection. The data collection tools are tests, observation sheets, and documentation. The results of data analysis from 21 students obtained classical completeness in the teacher's initial observation before using Project Based Learning model (PjBL), is 14.29%. The acquisition of the first cycle significantly increased with 52.38% classical completeness and was followed up in the second cycle with 90.48% classical completeness.